Selenium in white clover grass pasture for grazing lambs - Sormunen-Cristian, Riitta; Nykänen-Kurki, Päivi; Jauhiainen, Lauri (MTT, 2005)
In Finland, the use of white clover has recently increased especially in organic farming. However, information on its mineral content is very sparse. Therefore, contents of Ca, P, Mg, K and Se of white clover grass without nitrogen (CG0) and grass-only pastures with annual nitrogen rates of 0 (G0), 120 (G120) and 250 (G250) kg ha-1 were studied in organic soil. The pastures were grazed twice per season by growing lambs. Feed intake was determined by n-alkanes. The white clover contents averaged 36% and 42% in the first and the second grazing period. At the beginning of grazing the Se content averaged 0.19, 0.16, 0.29 and 0.29 ppm in CG0, G0, G120 and G250 pastures (p=0.01), respectively. When the season progressed, the Se content decreased in all pastures and averaged 0.015 ppm in late August. There was no difference in Se content between fertilized G120 and G250 pastures (0.09 ppm), but Se contents of unfertilized CG0 (0.07 ppm) and G0 pastures (0.06 ppm) were significantly (p<0.01) lower. The Ca and Mg contents and the Ca/P ratio were higher, and the K/(Ca+Mg) equivalent ratio lower in white clover grass than in grass-only swards. Daily Se supply was calculated according to herbage intake estimation and it averaged 0.09, 0.08, 0.11 and 0.12 mg per lamb in CG0, G0, G120 and G250 pastures, respectively. The daily Se requirement of sheep is 0.1-0.2 ppm and at minimum 0.06 ppm is needed for the prevention of white muscle disease. Except selenium the mineral composition was more balanced for growing lambs when white clover was added to grass pasture.
Keywords: Ka; grazing; legume; mineral content; sheep; sward; Trifolium repens